Gadamer for architects - Kidder, Paul (Thinkers for architects, 2013)
"Providing a concise and accessible introduction to the work of the twentieth century's celebrated German philosopher, Hans-Georg Gadamer, this book focuses on the aspects of Gadamer's philosophy that have been the most influential among architects, educators in architecture, and architectural theorists. Gadamer's philosophy of art gives a special place to the activity of "play" as it occurs in artistic creation, in language, and in thinking. His ideas on the function of symbols and meaning in art draw upon his teacher, Martin Heidegger, while developing further the applicability of Heideggerian thinking. His theory of interpretation, or "philosophical hermeneutics" offers profound ways to understand the influence of the past upon the present, and to appropriate the past in ever new forms. Gadamer's sensitivity to the way that theory arises out of practice and must maintain its relevance to practice gives his thought a remarkable usefulness and applicability. For architects, architectural theorists, architectural historians, and undergraduate and postgraduate students of architecture, Gadamer's thinking opens a world of possibilities for understanding how building today can be rich with human meaning, relating to architecture's history in an insightful manner that does not merely repeat nor merely repudiate that history"--